ARRONAX Cyclotron: Setting up of In-House Hospital Radiopharmacy. (10th March 2020) - Vidal, Aurelien; Bourdeau, Cécile; Frindel, Mathieu; Garcia, Tracy; Haddad, Ferid; Faivre-Chauvet, Alain; Bourgeois, Mickaël
Abstract : Whilst radiopharmaceuticals have an important role to play in both imaging and treatment of patients, most notably cancer patients, nuclear medicine and radiopharmacy are currently facing challenges to create innovative new drugs. Traditional radiopharmaceutical manufacture can be considered as either a routine hospital production or a large-scale industrial production. The gap between these two practices has meant that there is an inability to supply innovative radiopharmaceuticals for use at the local level for mono- or multicentric clinical trials with satisfactory quality and safety specifications. This article highlights the regulatory requirements in aseptic pharmaceutical processing and in nuclear medicine to be able to locally produce radiopharmaceuticals. We validate the proof-of-concept for an "in-house" hospital-based radiopharmacy including an on-site cyclotron, that can fulfill the conflicting requirements between radiation safety and aseptic processing. The ARRONAX in-house radiopharmacy is currently able to provide sterile and pyrogenic-free injectable radiopharmaceutical compounds for both industrial and institutional clinical trials.